Kemampuan Pemahaman Konsep Pada Pembelajaran Matematika Menggunakan Metode Penemuan Terbimbing Di SMA Negeri 14 Palembang - Rohman, Rohman; Syaifudin, Syaifudin; Astiswijaya, Nike (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2021)
This study aims to determine whether the ability to understand concepts of students who receive mathematics learning using the guided discovery method at SMA Negeri 14 Palembang is greater than the KKM score. The research methodology used is a quasi-experimental method with a one-shot case study design. Class X.2, which consisted of 40 students, was selected as the sample in this study. While the technique in data collection is a written test in the form of an essay. The test questions used in this study refer to indicators that have been set, namely indicators of problem solving abilities. The data analysis technique used t-test. Based on the results of the analysis of the test data, it was obtained that tcount = 2.196 and ttable = 1.683, so it can be concluded that the concept understanding ability of students who received mathematics learning using the guided discovery method at SMA Negeri 14 Palembang was greater than the KKM score